Micro Artificial Immune System for Traffic Light Control - Raul Galvan-Correa; Mauricio Olguin-Carbajal; Juan Carlos Herrera-Lozada; Jacobo Sandoval-Gutierrez; José Félix Serrano-Talamantes; Rodrigo Cadena-Martinez; Carlos Aquino-Ruíz (Applied Sciences, 2020)
A new bio-inspired meta-heuristic, called the micro artificial immune system (MAIS), has been developed in order to reduce the rates of pollution for a specific region of Mexico City through the optimization of vehicular flow. Simulation of urban mobility (SUMO) was used to simulate the effects of the programming of the traffic lights obtained by the MAIS. Currently, pollution and travel times from one place to another are increasing due to the number of inhabitants that live in big cities, which has generated a decrease in people’s quality of life. Hence, we propose the optimization of the programming of the sequences of traffic lights through this bio-inspired meta-heuristic. The obtained results show that the MAIS outperforms most of the algorithms tested in this research.